FRI0529 Analysis of the evolution of cortical and trabecular bone compartments in the proximal femur after spinal cord injury by 3d-dxa. (15th June 2017) - Gifre, L; Humbert, L; Muxi, A; Rio, L del; Vidal, J; Portell, E; Monegal, A; Guañabens, N; Peris, P
Abstract : Background: Spinal cord injury (SCI) is associated with a marked increase in bone loss and risk of osteoporosis development short-term after injury. 3D-DXA is a new imaging analysis providing volumetric measurements of the cortical and trabecular bone from DXA scans. Objectives: The aim of this study was to assess the evolution of 3D femoral shape, trabecular macrostructure and cortical bone from DXA scans in patients with recent SCI followed over 12 months. Methods: 16 males with recent SCI (<3 months since injury) were included. Clinical assessment, bone mineral density (BMD) measurements and 3D-DXA evaluation at proximal femur (analyzing the integral, trabecular and cortical volumetric BMD [vBMD] and cortical thickness) were performed at baseline and at 6 and 12 months of follow-up. Results: vBMD measured by 3D-DXA significantly decreased at integral, trabecular and cortical compartments at 6 months (-31.1 mg/cm 3, -8.8%, p<0.001; -25.4 mg/cm 3, -11.6%, p=0.001; and -20.4 mg/cm 3, -2.4%, p=0.004), with a further decrease at 12 months, resulting in an overall decrease of -58.9 mg/cm 3 (-16.6%, p<0.001), -47.9 mg/cm 3 (-21.9%, p<0.001) and -42.4 mg/cm 3 (-5%, p<0.001), respectively. Cortical thickness also decreased at 6 and 12 months (-8%, p<0.001; and -11.4%, p<0.001), with the maximal decrease being observed during the first 6 months. The mean BMD loss by DXA at femoral neck and total femur were -17.7% (p<0.001) and -21.1% (p<0.001), at 12-months, respectively. Integral vBMD values at baseline were positively correlated with total femur BMD (r=0.874, p<0.001), however no correlation was observed in the changes in these values at 12-months. Conclusions: 3D-DXA shows the differentiation of the marked bone loss that occurs at both proximal femoral compartments (cortical and trabecular) short-term after SCI. The present data suggest that 3D-DXA could be a useful complementary assessment tool in SCI patients. Disclosure of Interest: None declared